Stability of Pentoxifylline Injection: Application to Neonatal/Pediatric Care Setting - Senarathna, S.M.D.K.G.; Strunk, T.; Petrovski, M.; Batty, Kevin (ELSEVIER SCIENCE INC, 2021)
Pentoxifylline (PTX) is administered as 6- or 12-hour intravenous infusions in the treatment of sepsis or necrotizing enterocolitis in neonates; however, there is a paucity of formal stability data for PTX in the end-use solution. We investigated PTX stability in the simulated clinical conditions of neonatal intensive care, where PTX injection is diluted to 5 mg/mL and administered via syringe pump. A stability-indicating high performance liquid chromatography (HPLC) assay was established for PTX. The clinical simulation stability study comprised PTX 5 mg/mL in 20 mL syringes and was conducted at three temperatures, all protected from light: refrigerator (4°C); room temperature (22°C) and incubator/humidicrib (35°C). PTX stability also was evaluated at room temperature and exposed to light. Samples were drawn at pre-determined times over a 10 day period and stored frozen (-80°C) until assayed by HPLC. A single exponential equation was fitted to the concentration-time data to determine PTX stability. Forced degradation studies confirmed that PTX was stable at elevated temperature (up to 45°C), exposed to light and under acidic stress for up to 10 days, but subject to degradation under alkali and oxidative stress. PTX injection 5 mg/mL in 0.9% w/v sodium chloride or 5% w/v glucose was found to be stable when protected from light at 22°C and 35°C, and exposed to light at 22°C for at least 7 days. These data provide clinically relevant evidence that PTX injection is stable in the end-use, ICU/incubator clinical conditions for at least 24 hours.